Multisensory Imaginings: An Audionarratological Analysis of Philip Roth’s Novel Indignation and its German Radio Play Adaptation Empörung - Mildorf, Jarmila; Kinzel, Till (CounterText)

Orientfaszination im George-Kreis - Schönhärl, Korinna; Mangold-Will, Sabine (Kreis aus Kreisen. Der George-Kreis im Kontext deutscher und europäischer Gemeinschaftsbildung)

Pädagogische Professionalisierung als Kernelement der Qualifizierung studentischer Tutorinnen und Tutoren. Ein Praxisbericht - Striewisch, C.; Westphal, Petra (Berufsverband der Erziehungswissenschaftlerinnen und Erziehungswissenschaftler e.V. Der Pädagogische Blick. Zeitschrift für Wissenschaft und Praxis in pädagogischen Berufen)

Mentoring für Lehramtsstudierende – Konzeptentwicklung und -umsetzung - Stroot, T.; Westphal, Petra; Müsche, H. (Professionalisierung der Hochschuldidaktik. (Blickpunkt Hochschuldidaktik))

Coaching mit Jugendlichen beim Übergang von der Schule in die Ausbildung - Wiethoff, Christoph (Zur Differenzierung von Handlungsfeldern im Coaching: Die Etablierung neuer Praxisfelder)

Praxissemester in Paderborn gestartet - Umsetzung in den Bildungswissenschaften - Gehle, C; Rechel, S; Wiethoff, Christoph (Zeitschrift für Hochschulentwicklung)

Entwicklung eines kompetenzorientierten physikalischen Laborpraktikums - Sacher, Marc; Probst, Heike M.; Reinhold, Peter; Schaper, Niclas (Leitkonzepte der Hochschuldidaktik)

On the time transformation of mixed integer optimal control problems using a consistent fixed integer control function - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (Mathematical Programming)

A comparison of two predictive approaches to control the longitudinal dynamics of electric vehicles - Eckstein, Julian; Peitz, Sebastian; Schäfer, Kai; Friedel, Patrick; Köhler, Ulrich; Hessel von Molo, Mirko; Ober-Blöbaum, Sina; Dellnitz, Michael (Procedia Technology, 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)
In this contribution we compare two different approaches to the implementation of a Model Predictive Controller in an electric vehicle with respect to the quality of the solution and real-time applicability. The goal is to develop an intelligent cruise control in order to extend the vehicle range, i.e. to minimize energy consumption, by computing the optimal torque profile for a given track. On the one hand, a path-based linear model with strong simplifications regarding the vehicle dynamics is used. On the other hand, a nonlinear model is employed in which the dynamics of the mechanical and electrical subsystem are modeled.

Variational integrators of mixed order for dynamical systems with multiple time scales and split potentials - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (ECCOMAS Congress 2016 - Proceedings of the 7th European Congress on Computational Methods in Applied Sciences and Engineering)

Constrained Galerkin variational integrators and modified constrained symplectic Runge-Kutta methods - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (International Conference of Numerical Analysis and Applied Mathematics (ICNAAM))

Reduced order model based multiobjective optimal control of fluids - Peitz, Sebastian; Ober-Blöbaum, Sina; Dellnitz, M. (Proceedings of International Congress of Theoretical and Applied Mechanics)

Optimal control of switching times in switched linear systems - Stellato, B.; Ober-Blöbaum, Sina; Goulart, P.J. (2016 IEEE 55th Conference on Decision and Control (CDC))

Variational integrators of higher order for constrained dynamical systems - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (PAMM)

C1-continuous time integration based on cubic Hermite interpolation - Mergel, J.C.; Sauer, R.A.; Ober-Blöbaum, Sina (PAMM)

Time transformed mixed integer optimal control problems with impacts - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (PAMM)

Higher order variational integrators in optimal control theory - Ober-Blöbaum, Sina (PAMM)

Variational multirate integration in multi-body dynamics - Gail, T.; Leyendecker, S.; Ober-Blöbaum, S. (PAMM)

On higher order variational integrators and their relation to Runge-Kutta methods - Ober-Blöbaum, Sina (International Conference of Numerical Analysis and Applied Mathematics (ICNAAM))

Secure store and forward proxy for dynamic IoT applications over M2M networks - Díaz Sánchez, Daniel; Simon Sherratt, R.; Almenárez, Florina; Arias Cabarcos, Patricia; Marín, Andrés (IEEE Trans. Consumer Electron.)